SARS-CoV-2 Induces a More Robust Innate Immune Response and Replicates Less Efficiently Than SARS-CoV in the Human Intestines: An Ex Vivo Study With Implications on Pathogenesis of COVID-19Summary - Hin Chu; Jasper Fuk-Woo Chan; Yixin Wang; Terrence Tsz-Tai Yuen; Yue Chai; Huiping Shuai; Dong Yang; Bingjie Hu; Xiner Huang; Xi Zhang; Yuxin Hou; Jian-Piao Cai; et al. (Cellular and Molecular Gastroenterology and Hepatology, 2021)
Background and Aims: Besides prominent respiratory involvement, gastrointestinal manifestations are commonly reported in Coronavirus Disease 2019 (COVID-19) patients. We compared infection of ex vivo human intestinal tissues by SARS-CoV-2 and SARS-CoV with respect to their replication kinetics and immune activation profile. Methods: Human intestinal tissues were obtained from patients while undergoing surgical operations at Queen Mary Hospital, Hong Kong. Upon surgical removal, the tissues were immediately processed and infected with SARS-CoV-2 or SARS-CoV. Replication kinetics were determined with immunohistochemistry, qRT-PCR, and plaque assays. Immune activation in the infected intestinal tissues was assessed by detecting the gene expression of interferons and representative pro-inflammatory cytokines and chemokines. Results: SARS-CoV-2 could infect and productively replicate in the ex vivo human intestinal tissues with release of infectious virus particles, but not in ex vivo human liver and kidney tissues. Importantly, SARS-CoV-2 replicated less efficiently than SARS-CoV, induced less cytopathology in the human intestinal epithelium, and induced a more robust innate immune response including the activation of both type I and type III interferons, than SARS-CoV in human intestinal tissues. Conclusion: Using the ex vivo human intestinal tissues as a physiologically relevant model, our data indicated that SARS-CoV-2 could productively replicate in the human gut and suggested that the gastrointestinal tract might serve as an alternative route of virus dissemination. SARS-CoV-2 replicated less efficiently and induced less cytopathology than SARS-CoV in keeping with the clinical observations reported for COVID-19 and SARS, which might be the result of a more robust immune activation by SARS-CoV-2 than SARS-CoV in the human intestine.